Why did Socrates conduct his dialogues before an audience? - Keum, T (Imprint Academic, 2016)
The Socratic method is conventionally understood to be a one-on-one interaction between Socrates and an individual interlocutor. Why, then, does Socrates conduct so many of his dialogues in public places, where they are prone to being witnessed or even interrupted? Through a careful reading of the Gorgias, a dialogue traditionally appealed to in studies of both the Socratic method and the philosophy of rhetoric, I argue that Socrates deliberately involves his audience in his conversations with individuals. The Socratic method seeks to harness the group’s constructive potential in the formation of a temporary community around a joint philosophical inquiry.